The mitochondrial metabolic reprogramming agent trimetazidine as an 'exercise mimetic' in cachectic C26‐bearing mice. Issue 6 (11th November 2017) - Molinari, Francesca; Pin, Fabrizio; Gorini, Stefania; Chiandotto, Sergio; Pontecorvo, Laura; Penna, Fabio; Rizzuto, Emanuele; Pisu, Simona; Musarò, Antonio; Costelli, Paola; Rosano, Giuseppe; Ferraro, Elisabetta
Abstract: Background: Cancer cachexia is characterized by muscle depletion and exercise intolerance caused by an imbalance between protein synthesis and degradation and by impaired myogenesis. Myofibre metabolic efficiency is crucial so as to assure optimal muscle function. Some drugs are able to reprogram cell metabolism and, in some cases, to enhance metabolic efficiency. Based on these premises, we chose to investigate the ability of the metabolic modulator trimetazidine (TMZ) to counteract skeletal muscle dysfunctions and wasting occurring in cancer cachexia. Methods: For this purpose, we used mice bearing the C26 colon carcinoma as a model of cancer cachexia. Mice received 5 mg/kg TMZ (i.p.) once a day for 12 consecutive days. A forelimb grip strength test was performed and tibialis anterior, and gastrocnemius muscles were excised for analysis. Ex vivo measurement of skeletal muscle contractile properties was also performed. Results: Our data showed that TMZ induces some effects typically achieved through exercise, among which is grip strength increase, an enhanced fast‐to slow myofibre phenotype shift, reduced glycaemia, PGC1α up‐regulation, oxidative metabolism, and mitochondrial biogenesis. TMZ also partially restores the myofibre cross‐sectional area in C26‐bearing mice, while modulation of autophagy and apoptosis were excluded as mediators of TMZ effects. Conclusions: In conclusion, our data show that TMZ acts like an 'exercise mimetic' and is able to enhance some mechanisms of adaptation to stress in cancer cachexia. This makes the modulation of the metabolism, and in particular TMZ, a suitable candidate for a therapeutic rehabilitative protocol design, particularly considering that TMZ has already been approved for clinical use.